Endoxifen Approval for Bipolar Disorder in India: A Premature or a Pragmatic Decision?. Issue 1 (January 2023) - Gupta, Rishab; Singh, Swarndeep
Abstract: In this commentary, we critique the Indian government's decision to approve endoxifen for the treatment of acute mania among adults.